(untitled) (Modern education and development, 2025)
Transitioning from passive to active vocabulary use remains a significant challenge in second language education. Passive vocabulary refers to words learners understand when encountered, while active vocabulary pertains to words that can be produced effectively in speech and writing. While language learners often acquire passive vocabulary relatively easily, they may struggle to activate these words in meaningful communication. This article investigates the difficulties that pupils face in this process, examining the role of teaching methods, learner engagement, and cognitive processes in activating vocabulary. Through a review of current research and practical classroom examples, the study explores how deliberate practice, context-rich learning environments, and reflective activities can aid in transforming passive vocabulary into active use. The findings suggest that personalized learning approaches and strategic vocabulary tasks can significantly enhance students’ ability to incorporate new words into their active vocabulary repertoire.